A century of Arab politics from the Arab Revolt to the Arab Spring - Maddy-Weitzman, Bruce (Rowman & Littlefield, 2016)
From the "Great Arab Revolt" against Ottoman rule in World War I to the upheavals of the Arab Spring, this text analyzes a century of modern Arab history through the lens of three intertwined notions: the idea of a single Arab nation, the reality of multiple Arab states, and the competition between them over both concrete and symbolic interests.